PENGARUH FASHION PAKAIAN BANGKOK DAN MEDIA SOSIAL TIKTOK TERHADAP TREND FAST FASHION PAKAIAN DAN PERILAKU KONSUMTIF PADA GENERASI Z - Lailatul Maulidiah; Nur Rohmad Nuzil (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study was conducted to determine "The Influence of Bangkok Fashion Clothing and Tiktok Social Media on Fast Fashion Clothing Trends and Consumer Behavior in Generation Z". The strategy used in this study is a quantitative approach, with questionnaires as a data collection technique. The sampling method uses non-random sampling, namely each population does not have the same possibility of being sampled. The sample used was 100 respondents through questionnaires. The data analysis method used in this study was using the Partial Least Square (PLS) test tool. The results of this study indicate that Bangkok Fashion has a significant influence on Fast Fashion Clothing Trends. Based on P Values ​​0.000 <0.05. then H1 is accepted and H0 is rejected. It can be concluded that Bangkok Fashion is one of the fast fashion models that is popular with the public which is effective in influencing consumer attitudes and encouraging purchasing decisions. The results of this study provide important implications for generation Z to be wiser in shopping, in order to control consumer behavior in adolescence. Keywords: Social media, Consumer behavior, Fast fashion, Generation Z.